2010
DOI: 10.1017/s0790966700001154
|View full text |Cite
|
Sign up to set email alerts
|

Treatment considerations in clozapine induced enuresis or incontinence

Abstract: Antipsychotic related urinary symptoms are recognised and they remain a potential treatment-limiting sideeffect of clozapine. This article reports the incidence and management of two cases of clozapine-associated incontinence in psychiatrically stable patients. Both cases occurred during treatment and appear to have a similar pathophysiology, which may be related to the atypical nature of clozapine therapy. We searched the PubMed and MEDLINE databases for articles published from 1980 to 2008 that contain the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Clozapine dose ranged from 50 to 900 mg. Clozapine plasma levels were reported in seven patients and ranged from 290 to 760 ug/L. 14,[21][22][23][24] Seven studies were recorded in an inpatient setting, [23][24][25][26][27][28] and one in an outpatient setting, 29 whereas the remaining studies did not report the setting. Timing of enuresis ranged from 1 to 90 days after commencement of clozapine (median: 21 days).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clozapine dose ranged from 50 to 900 mg. Clozapine plasma levels were reported in seven patients and ranged from 290 to 760 ug/L. 14,[21][22][23][24] Seven studies were recorded in an inpatient setting, [23][24][25][26][27][28] and one in an outpatient setting, 29 whereas the remaining studies did not report the setting. Timing of enuresis ranged from 1 to 90 days after commencement of clozapine (median: 21 days).…”
Section: Resultsmentioning
confidence: 99%
“…All three patients experienced complete resolution of symptoms. One case used a dose of 500 mg three times a day, 14 and the other did not report the dose 21 . Neither study reported on adverse effects.…”
Section: Pharmacological Interventionsmentioning
confidence: 95%
See 3 more Smart Citations